2020
DOI: 10.1002/lary.29170
|View full text |Cite
|
Sign up to set email alerts
|

Office‐Based Procedure Training in Laryngology Fellowship Programs

Abstract: Objective To assess the current practices and challenges of training office‐based procedures to laryngology fellows in the United States. Methods An anonymous web‐based survey study was distributed to laryngology fellowship program directors, as listed by the American Laryngological Association. The survey was a 19‐item questionnaire with free‐text, Likert scale, and multiple‐choice answers. Results Twenty‐two of 27 program directors (81.4%) replied to the survey. Many programs (8/16) have three or more laryng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Otherwise, fellows largely assisted or observed procedures performed at lower volumes. In contrast, when fellowship directors were surveyed, it was concluded that the impact of weekly office procedure volume was favorable for fellowship training, although it had no effect over allowing trainees as primary surgeons 12 …”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Otherwise, fellows largely assisted or observed procedures performed at lower volumes. In contrast, when fellowship directors were surveyed, it was concluded that the impact of weekly office procedure volume was favorable for fellowship training, although it had no effect over allowing trainees as primary surgeons 12 …”
Section: Discussionmentioning
confidence: 95%
“…In contrast, when fellowship directors were surveyed, it was concluded that the impact of weekly office procedure volume was favorable for fellowship training, although it had no effect over allowing trainees as primary surgeons. 12 A notable exception to these trends involves laryngeal BoNT-A injection. This is a procedure performed at high volume (at least weekly) for most fellowship programs, but with which fellows reported inadequate opportunity to practice independently.…”
Section: Themes Suggestionmentioning
confidence: 99%
See 3 more Smart Citations